CHANGEMENTS CLIMATIQUES À L’ÉPREUVE DES QUERELLES ÉCOLOGIQUES : Évolution en dents de scie du concept «générations futures» en droit international de l’environnement. - CHALACHALA BONGALA, Nadyne-Clémence (IJRDO Journal of Forestry, wild life and Environment, 2019)
Environmental law is more than inventive except what it takes from other fields. Considering imagination, it is one of highest schools. That’s why it creates mechanisms as study of impact law, newest concepts as biodiversity, sustainable development, climate changes, incoming generations, common director principles as principles of prevention, precaution, polluter-payer, of information and participation. Up to the common and special law cleavage, Environmental Law creates, according to the movements of actors in order to make a complete and cleverly reality, which is traduced by the principle of conciliation. The sustainable development is both the lance iron and the future of that law: “satisfy actual generation’s needs without reducing the future generation’s chances to satisfy their”. This imperative of conciliation is expressed as general interest by the European court of human rights: “it is a deal to consider the quite equilibration to do between concurrent individual interests and the whole society”[1]. This study shows that climate changes has a link with the tomorrow of future generations whose life and happiness depend mostly to the environmental management of actual generations. [1]CEDH, idem.